2007
DOI: 10.1161/circulationaha.106.655076
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Very Low Plasma Concentrations of Troponin T in Patients With Stable Chronic Heart Failure

Abstract: Background-Circulating cardiac troponin T, a marker of cardiomyocyte injury, predicts adverse outcome in patients with heart failure (HF) but is detectable in only a small fraction of those with chronic stable HF. We assessed the prognostic value of circulating cardiac troponin T in patients with stable chronic HF with a traditional (cTnT) and a new precommercial highly sensitive assay (hsTnT). Methods and Results-Plasma troponin T was measured in 4053 patients with chronic HF enrolled in the Valsartan HeartFa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
464
5
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 644 publications
(521 citation statements)
references
References 46 publications
(41 reference statements)
32
464
5
13
Order By: Relevance
“…3,5,38) However, most studies of the prognostic value of cTnT in acute coronary syndrome, chronic heart failure and pulmonary embolism have found that the cTnT level at a single point is an independent predictor of future cardiac events. 2,4,[6][7][8]20,39) The rate of cTnT detected by the assay in the present study is very low in healthy adults. 17) Thus, we believe that elevated cTnT even at a single point has clinical significance.…”
Section: Therapeutic Implications Of Ongoing Myocardial Damage In Hy-contrasting
confidence: 47%
See 3 more Smart Citations
“…3,5,38) However, most studies of the prognostic value of cTnT in acute coronary syndrome, chronic heart failure and pulmonary embolism have found that the cTnT level at a single point is an independent predictor of future cardiac events. 2,4,[6][7][8]20,39) The rate of cTnT detected by the assay in the present study is very low in healthy adults. 17) Thus, we believe that elevated cTnT even at a single point has clinical significance.…”
Section: Therapeutic Implications Of Ongoing Myocardial Damage In Hy-contrasting
confidence: 47%
“…cTnT is a sensitive marker for the detection of myocardial damage in patients with not only acute coronary syndrome but also with chronic heart failure [2][3][4][5][6][7][8] and pulmonary embolism. 20) Therefore, some hypertensive patients might have ongoing myocardial damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16) Recently, a highly sensitive commercial assay of cTnI or cTnT is being widely used for cardiac injury evaluation. Latini, et al 17) reported that, with a standard assay, cTnT was detectable in 10% of patients with chronic HF but that, using a new hs-cTnT assay (Roche Diagnostics), it was detectable in 92% of HF patients. In our study, serum hs-cTnT values of 23% of HCM patients remained below the lower detection limit of the assay (0.003 ng/mL).…”
Section: Discussionmentioning
confidence: 99%